2015
DOI: 10.3389/fphys.2015.00004
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue activity as a target for the treatment of obesity/insulin resistance

Abstract: Presence of brown adipose tissue (BAT), characterized by the expression of the thermogenic uncoupling protein 1 (UCP1), has recently been described in adult humans. UCP1 is expressed in classical brown adipocytes, as well as in “beige cells” in white adipose tissue (WAT). The thermogenic activity of BAT is mainly controlled by the sympathetic nervous system. Endocrine factors, such as fibroblast growth factor 21 (FGF21) and bone morphogenic protein factor-9 (BMP-9), predominantly produced in the liver, were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
2
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 116 publications
(144 reference statements)
4
131
2
5
Order By: Relevance
“…In line with our results, the promotion of BAT activity or the browning of WAT has been reported to result in increased energy expenditure and protection against obesity and type 2 diabetes (35,36,52,53). These preclinical observations together with the recent discovery that browning of scWAT occurs in adult humans make this cell type an attractive therapeutic target for the treatment of obesity and type 2 diabetes (35,53,54). Our results suggest that molecules arising from the ALOX5/ALOX5AP pathway may have potential therapeutic effects.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with our results, the promotion of BAT activity or the browning of WAT has been reported to result in increased energy expenditure and protection against obesity and type 2 diabetes (35,36,52,53). These preclinical observations together with the recent discovery that browning of scWAT occurs in adult humans make this cell type an attractive therapeutic target for the treatment of obesity and type 2 diabetes (35,53,54). Our results suggest that molecules arising from the ALOX5/ALOX5AP pathway may have potential therapeutic effects.…”
Section: Discussionsupporting
confidence: 77%
“…2H). Under certain conditions, adipocytes within scWAT have the capacity to express UCP1 and may contribute to thermogenesis (35,36). These adipocytes share characteristics with brown adipocytes, in particular, their multilocular lipid droplet morphology, their high mitochondrial content, and the expression of a set of markers such as Ucp1, Cidea, or Ppargc1a (36).…”
Section: Ap2/alox5ap Transgenic Mice Are Leaner and Present Increasedmentioning
confidence: 99%
“…Unfortunately, there tends to be less functional brown adipose tissue in obese than in lean subjects. Therefore, it is important not only to acutely activate thermogenesis in brown adipocytes but also to increase their number and their capacity for thermogenesis [64]. Among the approaches being investigated are mimetics of irisin and fibroblast growth factor-21 [65,66], though recent work casts doubt on the role of irisin because many studies have used commercial ELISA kits to detect irisin that cross-react with other proteins [67].…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…On a C57BL/ 6/CBA background we have observed the recruitment of brown adipocytes in epididymal WAT of UCP1-tg mice evidenced by an increased respiratory capacity and induction of brown fat marker genes such as UCP1 and PGC1a (Keipert et al 2014). It is generally accepted that FGF21 induces this browning (Eckardt et al 2014;Poher et al 2015) which was also confirmed in UCP1-tg mice (Keipert et al 2014). Recruitable brown adipocytes within typical WAT depots [also named ''brite'', ''beige'' or ''inducible brown adipocytes'' (Harms and Seale 2013;Petrovic et al 2010;Schulz et al 2011)] were shown to be thermogenically functional (Shabalina et al 2013) and associated with improved metabolic profiles (Bartelt and Heeren 2014).…”
Section: Discussionmentioning
confidence: 80%